2018
DOI: 10.15294/jpii.v7i2.14232
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Scientific Explanation in Blended Physics Learning with E-Scaffolding

Abstract: This purpose of this research was to analyze the influence of blended physics learning with e-scaffolding on the gas kinetic theory to the students’ scientific explanation. This research used quasi-experimentation with one group pretest-posttest design. The population of this research included the grade XI students of Natural Sciences in SMA Negeri 1 Bangkalan. The proposed hypothesis was that the blended physics learning with e-scaffolding affected the students’ scientific explanation. The research results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Hong and Xinyi (2019) showed that online learning resources could help to achieve learning goals. The research results by Oktavianti et al (2018) showed that students' scientific explanation skills significantly increase after they experience blended learning physics with e-scaffolding. Wang (2019) showed that blending learning has a significant effect on increasing the effectiveness of digital art teaching.…”
Section: Introductionmentioning
confidence: 98%
“…Hong and Xinyi (2019) showed that online learning resources could help to achieve learning goals. The research results by Oktavianti et al (2018) showed that students' scientific explanation skills significantly increase after they experience blended learning physics with e-scaffolding. Wang (2019) showed that blending learning has a significant effect on increasing the effectiveness of digital art teaching.…”
Section: Introductionmentioning
confidence: 98%
“…This virtual laboratory can be used in the process of learning and discussion to strengthen the concepts and knowledge related to modern physics which are generally invisibly microscopic. Oktavianti et al (2018) also found that blended physics learning with e-scaffolding enhanced the students' scientific explanation such as claim, evidence, and reasoning. Blended learning is relevant to be implemented in Indonesian higher education to reinforce students to learn self-reliantly beyond the classroom, build the competence to collaborate and discuss with their peers in order to solve problems (Zainuddin & Keumala, 2018).…”
Section: Introductionmentioning
confidence: 82%
“…However, students who were given scaffolding had a better explanation than those who were given written instructions. Additionally, a study by Oktavianti et al (2018) reported that the students' scientific explanation ability increases after they learn in blended learning with scaffolding.…”
Section: Discussionmentioning
confidence: 99%
“…A scientific explanation is a crucial issue that needs to be investigated immediately. Scientific explanation Several previous studies have investigated scientific explanations or scientific arguments (De Andrade et al, 2019;Gilles & Buck, 2019;Herman et al, 2019;Koppal et al, 2020;Lee et al, 2019;Oktavianti et al, 2018;Pallant & Lee, 2015;Wagner et al, 2020). The results of those studies show that good student's scientific explanations support in-depth understanding, and the provision of scaffolding by educators can develop students' scientific explanations.…”
Section: Introductionmentioning
confidence: 99%